2020
DOI: 10.1111/1759-7714.13485
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib can overcome acquired resistance to EGFR‐TKIs via FGFR1 signaling in non‐small cell lung cancer without harboring EGFR T790M mutation

Abstract: BackgroundAlthough many studies have defined mechanisms of resistance to EGFR‐TKIs, acquired resistance remains the major limitation of monotherapy with EGFR‐TKIs.MethodsCell viability was analyzed using a Cell Counting Kit‐8 (CCK‐8) assay. EGFR T790M mutation was sequenced on a HiSeq 4000 platform. mRNAs from HCC827 and HCC827 gefitinib‐resistant (GR) cells were analyzed by genome analyzer‐based deep sequencing. The effect of anlotinib on apoptosis and cell cycle arrest of HCC827 GR was detected by fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…These data suggest that anlotinib-induced apoptosis may be the result of elevated intracellular ROS, which may function as upstream regulators of the p38/JNK MAPK and ERK pathways. In contrast, other studies have shown that anlotinib attenuates ERK activation in diverse cancer cells (Yang Q. et al, 2020;Hu et al, 2020;Lian et al, 2020). Cagnol et al reported that ERK activity depends on the presence of ROS (Cagnol and Chambard, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…These data suggest that anlotinib-induced apoptosis may be the result of elevated intracellular ROS, which may function as upstream regulators of the p38/JNK MAPK and ERK pathways. In contrast, other studies have shown that anlotinib attenuates ERK activation in diverse cancer cells (Yang Q. et al, 2020;Hu et al, 2020;Lian et al, 2020). Cagnol et al reported that ERK activity depends on the presence of ROS (Cagnol and Chambard, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…PC9GR and HCC827GR cells were highly insensitive to gefitinib compared to their respective parental cells (Additional file 2 : Fig S1). Our previous work showed that the PC9GR cell line harbours EGFR 19del and T790M mutations; the HCC827GR cell line harbours the EGFR 19del mutation and overexpresses FGFR1 and AXL [ 26 , 27 ]. To investigate whether there are other mechanisms responsible for acquired resistance to EGFR-TKIs in addition to variations such as the T790M mutation, MET amplification and overexpression of FGFR1 and AXL, we examined expression of soluble receptors and related proteins in PC9GR and HCC827GR cells by proteome profiler array analysis.…”
Section: Resultsmentioning
confidence: 99%
“…5 b). Given that osimertinib is an oral, irreversible EGFR-TKI that is selective for both EGFR and T790M resistance mutations [ 32 ], we also evaluated p-FAK in T790M mutant cells (PC9GR and H1975) treated with osimertinib [ 25 , 27 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main acquired resistance mechanisms appear to be secondary mutations of EGFR (T790M), KRAS , PIK3CA and MET amplification. A recent study suggested that anlotinib could overcome acquired resistance to EGFR-TKI via inhibiting FGFR1 ( 31 ). A preclinical study showed that anlotinib could inhibit proliferation and induce apoptosis of KRAS mutation lung cancer cells through downregulating MEK and ERK.…”
Section: Discussionmentioning
confidence: 99%